A Literature Review: Risk Factors for Gastritis Incidence in the Coastal Region Served by Tampo Health Center - Annisa Aulliyah; Sry Nazirah; Nur Juliana (Journal of Health Science and Pharmacy, 2025)
Background: Gastritis, or inflammation of the gastric mucosa, is a common global health problem, including in Indonesia. Coastal populations have a higher vulnerability to this disease due to a combination of lifestyle, environmental, and socioeconomic factors. Irregular eating patterns, frequent consumption of spicy or acidic foods, smoking, and coffee consumption are major contributing factors. Additionally, heavy labor such as fishing and malnutrition further increase the risk in this population. Objective: The objective of this study is to evaluate the risk factors for gastritis through a systematic literature review of 15 studies published between 2018 and 2024. Method: This study employed a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. Data were collected from 15 relevant research articles published between 2018 and 2024. Results: The main risk factors for gastritis include irregular eating patterns, consumption of spicy or acidic foods, smoking, and coffee intake. Low socioeconomic status and physically demanding occupations, such as fishing, exacerbate vulnerability. Coastal adolescents with low energy intake have a fourfold higher risk of developing gastritis. Stress increases the risk of gastritis by 2.8 times. Health education interventions have been shown to improve public understanding, with knowledge scores increasing from 43 to 76 points. Conclusion: Gastritis in coastal regions is a multifactorial health problem influenced by lifestyle, socioeconomic, and psychological factors. Comprehensive prevention strategies should include nutritional education, stress management, and improved access to quality healthcare services. Keywords: Gastritis; eating patterns; stress; coastal; risk factors